Berkenalan Dengan Siklus Akuntansi Bersama Siswa Yayasan Prima Unggul - Nugroho, Vidyarto; Weruin, Urbanus Ura (Journal Of Human And Education (JAHE), 2025)
In an increasingly competitive local and global economic climate, trading companies play an important role in supporting economic growth, creating jobs, and bringing prosperity to the community. The main objective of a trading company is to collect goods and services from producers to be distributed to consumers in order to make a profit. In carrying out this activity, the role of accounting is very crucial. Accounting is needed by management and stakeholders in order to make financial decisions transparently, quickly, accurately, efficiently, and profitably. Knowledge and understanding of the accounting cycle need to be possessed by workers or prospective workers in order to play an optimal role in achieving the future. In order to provide in-depth knowledge and understanding of the accounting cycle in trading companies, we conduct Community Service Program (Pengabdian Kepada Masyarakat-PKM) in the form of training on the accounting cycle to high school and vocational school students under the Prima Unggul Foundation. The materials presented in this training include: the trading company accounting cycle, financial transactions and evidence, journal entries, to the preparation of financial reports including profit and loss reports, capital change reports, financial position reports, and cash flow reports. Through creative, innovative, interactive, and real training methods (case studies), students who take part in this training are not only enthusiastic about taking part in the training but are also able to answer questions in discussions and complete accounting case examples. The training, which was held through Zoom Meeting, succeeded in equipping participants with knowledge and its application in trade accounting practices. As many as 90% of participants stated that the material presented in this training was important, relevant, and useful for them to understand accounting practices in order to achieve a better future.